2009
DOI: 10.1177/0363546509339915
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Platelet Composite Enhances Biomechanical and Histologic Healing of the Porcine Anterior Cruciate Ligament

Abstract: Background-The anterior cruciate ligament (ACL) fails to heal after traumatic rupture. Furthermore, large-animal models have recently shown that 1-month functional ACL healing is augmented after suture repair when a bioactive scaffold is placed in the tear site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
182
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(188 citation statements)
references
References 54 publications
3
182
0
Order By: Relevance
“…A suture repair was performed and then a collagen-platelet scaffold was placed in the gap between the two severed ends of the ligament (a technique called the bio-enhanced suture repair). Using this model, we found that placement of a collagen-platelet scaffold in the wound site of the ACL could stimulate both histologic and biomechanical healing of the ligament 76 and that, by three months, the strength of the ACL treated with a bio-enhanced repair technique was similar to that previously reported for ACL reconstruction in similar animal models 77 . Interestingly enough, when either a collagen scaffold alone 78 or a platelet solution alone 79 was used as the bio-enhancement, there was no statistically significant improvement over suture repair alone.…”
Section: Use Of Concentrated Autologous Bone-marrow Stem Cells For Thsupporting
confidence: 78%
“…A suture repair was performed and then a collagen-platelet scaffold was placed in the gap between the two severed ends of the ligament (a technique called the bio-enhanced suture repair). Using this model, we found that placement of a collagen-platelet scaffold in the wound site of the ACL could stimulate both histologic and biomechanical healing of the ligament 76 and that, by three months, the strength of the ACL treated with a bio-enhanced repair technique was similar to that previously reported for ACL reconstruction in similar animal models 77 . Interestingly enough, when either a collagen scaffold alone 78 or a platelet solution alone 79 was used as the bio-enhancement, there was no statistically significant improvement over suture repair alone.…”
Section: Use Of Concentrated Autologous Bone-marrow Stem Cells For Thsupporting
confidence: 78%
“…Comparisons of healing of the anterior cruciate ligament with that of the medial collateral ligament, which spontaneously heals, have led to the hypothesis that the deficiency in anterior cruciate ligament healing is due to incomplete scaffold formation within the injury site 3,4 . As a result, an enhanced anterior cruciate ligament repair technique, in which a scaffold is surgically placed in the gap between the torn ends of the ligament to provide a provisional structure on which new tissue can develop, has shown promise in preliminary animal studies [5][6][7] . A collagen-platelet composite has recently been shown to provide a suitable provisional scaffold that stimulates functional healing of the anterior cruciate ligament in large animal models [5][6][7] .…”
mentioning
confidence: 99%
“…As a result, an enhanced anterior cruciate ligament repair technique, in which a scaffold is surgically placed in the gap between the torn ends of the ligament to provide a provisional structure on which new tissue can develop, has shown promise in preliminary animal studies [5][6][7] . A collagen-platelet composite has recently been shown to provide a suitable provisional scaffold that stimulates functional healing of the anterior cruciate ligament in large animal models [5][6][7] . The influence of age and skeletal maturity on the ability of the anterior cruciate ligament to heal has not been thoroughly characterized.…”
mentioning
confidence: 99%
“…The use of cells as biological vehicles [6][7][8][9][10] or of growth factors [11,12] has been shown to enhance ligament healing. Recently, the use of a bioactive collagenbased scaffold infiltrated with platelets has yielded a positive effect on the healing of an ACL graft [13]. These data emphasise the importance of cellular and molecular mechanisms in the process of ligament healing and more generally in the field of regenerative orthopaedics [14].…”
Section: Introductionmentioning
confidence: 99%